Anti-Inflammatory Activity of Ethanol And Fraction of Buni Leaves (Antidesma Bunius L.) on White Rat In Carrageenan Induced Paw Inflammation - Kautsar, Lintang; Sitorus, Panal; Dalimunthe, Aminah (Asian Journal of Pharmaceutical Research and Development, 2019)
Objectives: The purpose of this study was to investigate the anti-inflammatory effect ethanol extract and fraction of buni leaves (Antidesma bunius L.) in term of decreased edema volume of male white rat in 1% carrageenan-induced and also to determine the effective dose Design: The design of this study was experimental, where the extraction and fraction of buni leaves were tested for inflammation inhibition value ​​in carrageenan-induced white rats.The inflammatory activity test was divided 6 groups. The Group I (negative control) was given CMC 0.5%, Group II (positive control) was given diclofenac sodium 2,25 mg/kg bw (body weight), while Group III, IV, V and VI were given buni leaves extract and fraction at a dose of 100, 200 and 400 mg/kgbw respectively Interventions: The variable that was intervened in this study was the concentration of extract used Main outcome measure: The main measurement results in this study were to know the extracts and fractions which are capable inhibitor volume of edema in the carrageenan-induced rat paw Results: the anti-inflammatory effects from buni leaves exhibited the most effective activity to reduce edema in the rat paw i.e. EEDB 200 mg / kg bw and FEADB 200 mg / kg bw showing the same value of against positive control Conclusion: ethanol extract and ethyl acetate fraction buni leaves(Antidesma bunius L.) has an effective anti-inflammatory activity at a dose of 200 mg/kg bw.